ChemInform Abstract: A Cascade Approach to Fused Indolizinones Through Lewis Acid—Copper(I) Relay Catalysis. Issue 31 (11th July 2013) - Huang, Huawen; Ji, Xiaochen; Wu, Wanqing; Jiang, Huanfeng
Abstract A novel synthesis of fused indolizidinones from cyclopropyl ketones and nitriles using a Lewis acid‐Cu(I) binary catalytic system is described.